RANCANG BANGUN SISTEM SMART ROOMS BERBASIS INTERNET OF THINGS PADA AKOMODASI KAPAL FLOATING CRANE - Rizki Maulana Yusron; Saiful Irfan; Sonhaji Sonhaji; Akhmad Kasan Gupron (JURNAL ILMIAH NUSANTARA, 2024)
The smart room concept aims at energy efficiency by integrating natural and artificial lighting systems through automatic control and sensors by determining the types of sensors used, the smart room concept provides an efficient solution for managing buildings, such as ships, by integrating automatic technology to control the lighting system, burning, and others. Smart spaces leverage computers and the Internet of Things (IoT) to increase comfort and efficiency, at a lower cost than traditional systems. The method used by this panel of researchers uses a prototype as a system development that uses an approach to create a program quickly and gradually so that it can immediately be evaluated by users. In order to obtain data in completing this research, the writer used direct field research techniques in ship accommodation which still uses a manual system in the room. The results of this research were obtained from the design of hardware and software in a smart room which developed an LDR sensor to turn on the lights automatically at night, a PIR sensor to turn on the AC when it automatically detects someone's presence, an ultrasonic sensor to turn on the faucet automatically and uses CCTV that can rotate 3600. The smart room can carry out monitoring using IoT which can be controlled by the ESP12F, which communicates with the Arduino Uno via the Serial Monitor feature for data exchange. Remote control via the third party application Blynk ran smoothly without significant problems and the test results were declared valid..